Employees Reaction to Selection Process and Its Effect on Behavioural Outcomes in Organizations of Nepal - Vaidya, Prabina Rajbhandari (Journal of Business and Management, 2022)
Background: Limited prior research has focused on social aspect of recruitment and selection (R&S) process: the behavioral outcomes, the effect of perceptions of selection process, decisions made by new employees and its effect on the organization.Objectives: This study aims to analyze employees’ perception to recruitment and selection process and resultant behavioral and attitudinal outcomes in organizations in Nepal and also examines the moderation effect of PJF.Methods: The study follows quantitative-hypothetico-deductive research methodology. Altogether 210 employees from public and private organizations of Nepal participated in the study. Moderated multiple regression was used to test hypotheses and moderation effect.Results: Regression result shows significant and positive relation between R&S process- PPV, TPJ and RI with outcome variables OC and OE and significant negative relation with TI. Moderating effect was seen in the relation between PPV, PJF and OC.Conclusion: R&S process in organizations should be fair. This process if perceived as unfair by applicants, there is high degree of turnover once they are employed. This has high cost on organizations and also loss of competent and talented employees.